Enlarging the Eyebox of Maxwellian Displays with a Customized Liquid Crystal Dammann Grating - Ziqian He; Kun Yin; Kuan-Hsu Fan-Chiang; Shin-Tson Wu (Crystals, 2021)
The Maxwellian view offers a promising approach to overcome the vergence-accommodation conflict in near-eye displays, however, its pinhole-like imaging naturally limits the eyebox size. Here, a liquid crystal polymer-based Dammann grating with evenly distributed energy among different diffraction orders is developed to enlarge the eyebox of Maxwellian view displays via pupil replication. In the experiment, a 3-by-3 Dammann grating is designed and fabricated, which exhibits good efficiency and high brightness uniformity. We further construct a proof-of-concept Maxwellian view display breadboard by inserting the Dammann grating into the optical system. The prototype successfully demonstrates the enlarged eyebox and full-color operation. Our work provides a promising route of eyebox expansion in Maxwellian view displays while maintaining full-color operation, simple system configuration, compactness, and lightweight.